Gestión administrativa en la cooperativa de transporte san francisco del cantón pueblo viejo - Zambrano García, Polett Zoraida (2022)
The development of this case study is based on determining what are the drawbacks present with respect to the administrative management of the San Francisco transport cooperative, having as a research methodology the application of the quantitative method, using as a technique of gathering information the execution of a survey, directed to the collaborators of the mentioned entity, with the purpose of knowing exactly the present problem.